Effect of Nd:YAG Irradiation and Fluoride Application on Dentine Resistance to Erosion in Vitro - Magalhaes, Ana Carolina [UNESP]; Rios, Daniela; De Andrade Moreira Machado, Maria Aparecida; Bonifacio da Silva, Salete Moura; Zanirato Lizarelli, Rosane de Fatima; Bagnato, Vanderlei Salvador; Rabelo Buzalaf, Marilia Afonso (Mary Ann Liebert, Inc., 2008)
Objective: In this paper we evaluated the effect of two fluoridated agents and Nd:YAG irradiation separately and in combination on dentine resistance to erosion. Background Data: The morphological changes in dentin induced by laser treatment may reduce the progression of erosive lesions. Due to the possibility of a synergistic effect of laser with fluoride, this study was conducted. Materials and Methods: Eighty bovine dentine samples (4 x 4 mm) were randomly divided into eight groups, according to the following treatments: G1: untreated (control); G2: acidic phosphate fluoride gel (APF 1.23%) for 4 min; G3: fluoride varnish (NaF 2.26%) for 6 h; G4: 0.5 W Nd: YAG laser (250 mu sec pulse, 10 Hz, 35 J/cm(2), 30 sec); G5: 0.75 W Nd: YAG laser (52.5 J/cm(2)); G6: 1.0 W Nd: YAG laser (70 J/cm(2)); G7: APF + 0.75 W Nd: YAG laser; and G8: NaF + 0.75 W Nd: YAG laser. After the treatments, half of each dentine surface was protected with nail varnish. The samples were stored in artificial saliva (30 mL/sample) for 24 h and submitted to four erosive 1-min cycles. Between the erosive attacks, the blocks were maintained in artificial saliva for 59 min. The erosive wear was evaluated by profilometry. Results: The mean wear (+/- SD, mu m) was: G1: 1.20 +/- 0.20; G2: 0.47 +/- 0.06; G3: 0.81 +/- 0.11; G4: 1.47 +/- 0.32; G5: 1.52 +/- 0.24; G6: 1.49 +/- 0.30; G7: 0.49 +/- 0.11; and G8: 1.06 +/- 0.31 (Tukey's test, p < 0.05). Conclusions: Laser irradiation was not able to reduce dentine erosion. However, fluoride application was able to increase the dentine's resistance to erosion, and APF showed better results than fluoride varnish.